Penerapan Strategi Pembelajaran dalam Pemahaman Makna Harfiah dan Majazi di Lembaga SMP Pesantren Zainul Hasan Genggong - Muzdalifah Muzdalifah; Ainur Rofiq Sofa (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study aims to describe effective learning strategies in increasing the understanding of literal meaning and majazi at students at Zainul Hasan Ganggong Islamic Boarding School. Pesantren, as a religious-based education institution, has an important role in shaping comprehensive religious understanding, including understanding of rich religious texts about literal meaning and majazi. This study used a descriptive qualitative approach with observation methods, interviews, and documentation to collect data. The results showed that effective learning strategies include the use of tahsin methods (proper and correct reading of the Qur'an), tahfizh (memorizing the Qur'an), a contextual explanation of the Qur'an and hadith verses, as well as group discussions that encourage students to interact and exchange thoughts. These strategies have proven to increase students’ understanding of literal meaning and majazi, so they can understand more deep and cyclic texts in their daily lives. This study provides important implications for curriculum development and learning methods in pesantren to improve the quality of the religious understanding of students.